Managerial economics - Png, Ivan. (Blackwell, 1998)
Introduction to managerial economics. Demand. Quantitative demand analysis. Supply. Competitive markets. Economic efficiency. Costs. Monopoly. Pricing policy. Strategic thinking. Externalities. Asymmetric information. Incentives and organization. Regulation.